2023
DOI: 10.1093/europace/euac245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for delivering cardiac resynchronization therapy: an acute electrical and haemodynamic within-patient comparison of left bundle branch area, His bundle, and biventricular pacing

Abstract: Aims Left bundle branch area pacing (LBBAP) is a promising method for delivering cardiac resynchronization therapy (CRT), but its relative physiological effectiveness compared with His bundle pacing (HBP) is unknown. We conducted a within-patient comparison of HBP, LBBAP, and biventricular pacing (BVP). Methods and results Patients referred for CRT were recruited. We assessed electrical response using non-invasive mapping, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…This is in line with a recent study, which found that LBBAP was not inferior to HSP with respect to LV function, but both HBP and LBBAP outperformed BiVP in terms of haemodynamic improvement. 31 However, sLBBP without fusion led to a non-physiological late activation of the RV, which has also been reported in other studies. 31 , 32 This late RV activation effectively replicated an right bundle branch block-like pattern leading to an increased load on the RVfw.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is in line with a recent study, which found that LBBAP was not inferior to HSP with respect to LV function, but both HBP and LBBAP outperformed BiVP in terms of haemodynamic improvement. 31 However, sLBBP without fusion led to a non-physiological late activation of the RV, which has also been reported in other studies. 31 , 32 This late RV activation effectively replicated an right bundle branch block-like pattern leading to an increased load on the RVfw.…”
Section: Discussionsupporting
confidence: 77%
“… 31 However, sLBBP without fusion led to a non-physiological late activation of the RV, which has also been reported in other studies. 31 , 32 This late RV activation effectively replicated an right bundle branch block-like pattern leading to an increased load on the RVfw. Furthermore, sLBBP is an unstable condition and will likely progress to nsLBBP, 33 also making it clinically unfeasible.…”
Section: Discussionsupporting
confidence: 77%
“…We performed an in silico electrophysiology clinical trial to study the Although selective HBP was reported to shorten and sometimes normalize the QRS duration, 6,22 many patients are left with partial dyssynchrony. HBP effectiveness relies on the assumption that most blocks happen proximally along the His bundle.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed LV synchrony by computing 95% of LV activation time (LVAT‐95), computed as the shortest interval to activate 95% of the LV, and the LV dyssynchronous index (LVDI), defined as the standard deviation of LV activation times. Both LVAT‐95 and LVDI have been used in the literature to quantify response to pacing from ECGi data 22 . Similarly, BIV dyssynchrony was quantified by computing 90% of biventricular activation time (BIVAT‐90) and the biventricular dyssynchronous index (BIVDI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation